University Library at a New Stage of Social Communications Development. Conference Proceedings. No IV (2019) - (:unkn) unknown (Dnipro National University of Railway Transport named after Academician V. Lazaryan, Dnipro, 2019)
ENG: The journal is a peer-reviewed edition that supports a policy of open access to scientific publications and publishers articles under a Creative Commons Attribution 4.0 International License. Field of science and issues in focus: Journal of Conference proceedings depict the latest achievements in the research of library and information science - revealing emerging trends and new ideas before they appear in journals. Journal of Conference proceedings offer broad coverage of new ideas, methodologies and projects in fast-moving areas of research related to the activity of university libraries in education, science and culture.

UKR: Щорічник є рецензованим виданням, що підтримує політику відкритого доступу до наукових публікацій і статей видавців за міжнародною ліцензією Creative Commons Attribution 4.0. Сфера науки та проблеми: статті конференції відображають останні досягнення в дослідженнях і практиці в галузі бібліотечної та інформаційної справи - розкривають нові тенденції й нові ідеї до того, як вони з'являються в журналах. Матеріали конференції пропонують широке охоплення нових ідей, методологій і проектів в швидко мінливих областях досліджень і практики, пов'язаних із діяльністю університетських бібліотек в галузі освіти, науки і культури.
Бібліотека університету на новому етапі розвитку соціальних комунікацій. Матеріали конференції. No IV (2019)
Keywords: university library; publishing activity; website; academic libraries; quality; Scopus; education; UDC; information technologies; marketing; open access; license Creative Commons Attribution 4.0; бібліотека університету; видавнича діяльність; веб-сайт; академічні бібліотеки; якість; освіта; УДК; інформаційні технології; маркетинг; відкритий доступ; ліцензія Creative Commons Attribution 4.0; НБ